Benthic Biocriteria Assessment of the Lower Roanoke River, North Carolina: A Final Report to Weyerhaeuser Paper Company - Cooper, John E.; Rulifson, Roger (East Carolina University, 1993)
Recent changes in environmental monitoring procedures of industrial activities suggest that future environmental assessments will be made using biocriteria methodology. Benthic macroinvertebrates have been the most often used group of organisms in assessing water quality. This study was conducted to determine the present composition of the benthic macroinvertebrate community and to evaluate the results using several biological indices that will likely form the basis for the development of biocriteria.
ICMR Contribution Series, NO. ICMR-93-03